Analysis of risk factors in patients admitted with epistaxis - Maqbool, Tabish; Qadri, Sajad; Showkat, Showkat Ahmed; Ahmed, Rauf; Mehta, Kulvinder Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Epistaxis can be classified into anterior and posterior epistaxis. All bleeding occurs as a result of disruption of the intact nasal mucosa, whether due to trauma, inflammation, or neoplasm. Management depends on the severity of the bleeding and its underlying cause. Methods: This study was done in department of otorhinolaryngology in a tertiary care centre from September 2018 to December 2020. A total of 143 patients were studies. All patients admitted in our department as a case of epistaxis were analysed for the risk factors present in them which could be the cause of epistaxis. Results: In our study it was seen the risk factor involved in majority of patients was hypertension (70%), followed closely by diabetis mellitis and deranged coagulogram (65%). Chronic kidney disease was an associated risk factor in 64% of patients. All these factors cause microangiopathies which in turn lead to bleeding. Conclusions: The current study can be taken as indirect evidence that while raised blood pressure is seen in patients with severe epistaxis but in general the diseases associated with microangiopathies.